(untitled) (International Journal of Engineering and Computer Science, 2017)
The main objective is to provide comfort to the mobile users by providing online information about various cities in TAMILNADU. The band width provided by the early networks are less leading to the network traffic and reduced data rate. In the past few years, circuit-switched networks showed a tremendous growth in data traffic due to the increasing popularity of the internet. Service providers need effective means to share the scarce radio resources between many subscribers. In a circuit- switched mode, a channel is allocated to a single user for the duration of the connection. Consequently new data applications are emerging and are reaching the mobile users. The existing mobile applications provide a text based information directory which is WAP (Wireless Application Protocol). The same can be developed as a GPRS (General Packet Radio Service) application that uses the global internet gateway through which it can be accessed in mobile devices.